2020
DOI: 10.3389/fgene.2020.562114
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1291 Is Associated With Locoregional Metastases in Patients With Early-Stage Breast Cancer

Abstract: Evidence that microRNAs (miRNAs) regulate the various steps of metastasis is increasing. Several studies have looked at the miRNA expression profile in primary breast tumors but few have compared primary tumor and sentinel lymph node (SLN) metastasis. We correlated the expression of miRNAs with the SLN status and the outcome of axillary lymph node dissection (ALND) in 60 patients with early breast cancer. We profiled the expression of miRNAs in paired breast tumor samples and SLNs using the NextSeq500 Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…In this study, a panel of four miRNAs (miR-1291, miR-217, miR-455-3p, and miR-566) was identified as a novel diagnostic biomarker for AMI after an integrated analysis of two microarray results and a comparison of their AUC values using ROC analysis. Regarding the four miRNAs set, miR-1291 was found to have regulatory effects in many tumors (Escuin et al, 2020 ). On its side, miR-217 inhibits apoptosis of atherosclerotic endothelial cells via the TLR4/PI3K/Akt/NF-κB pathway (Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a panel of four miRNAs (miR-1291, miR-217, miR-455-3p, and miR-566) was identified as a novel diagnostic biomarker for AMI after an integrated analysis of two microarray results and a comparison of their AUC values using ROC analysis. Regarding the four miRNAs set, miR-1291 was found to have regulatory effects in many tumors (Escuin et al, 2020 ). On its side, miR-217 inhibits apoptosis of atherosclerotic endothelial cells via the TLR4/PI3K/Akt/NF-κB pathway (Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a class of small non-coding RNA molecules, are 19–25 nucleotides in length and regulate gene expression at the post-transcriptional level through direct binding to the 3′-UTR of target mRNAs, leading to the inhibition of mRNA translation or mRNA degradation (Filipowicz et al, 2008 ). At present, the number of human miRNAs exceeds 1,900, and the number of target genes is predicted to be in the range of 1,000 s. Some estimates indicate that miRNAs target more than 30% of the human genome (Escuin et al, 2020 ). MiRNAs can be produced by all cell types and come from a variety of cell sources, such as endothelial cells, monocytes and macrophages, vascular smooth cells and platelets, and possibly secreted in the blood encapsulated in microparticles (exosomes, microvesicles, and apoptotic bodies), or combined with proteins or high-density lipoproteins (HDL) (Navickas et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatic pathway analysis predicted that sd/miR-1291 regulates WNT signaling, planar cell polarity/convergent extension (PCP/CE) pathway, β-catenin independent WNT signaling, diseases of signal transduction, and signaling by receptor tyrosine kinases (RTKs), among others. While these results strongly suggest that sd/miR-1291 is a tumor-suppressing RNA, patient survival analysis revealed that expression of this sdRNA alone could not significantly predict patient survival [ 63 ].…”
Section: Sdrnas In Cancermentioning
confidence: 99%
“…MicroRNA (miRNA, miR) are involved in the pathological development and metastasis of cancer [16,17]. Several natural products showed an anti-cancer effect by regulation of cancer-related miRNAs.…”
Section: Introductionmentioning
confidence: 99%